Radionuclide imaging of HER2/neu expression in metastatic axillary lymph nodes in breast cancer patients: comparing the efficacy of [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE)3-G3 - О. D. Bragina; L. А. Tashireva; Е. Yu. Garbukov; М. А. Vostrikova; А. А. Romanova; S. М. Deyev; М. Е. Borodina; V. I. Chernov (Бюллетень сибирской медицины)
Aim. To conduct a direct comparative analysis of single-photon emission computed tomography (SPECT-CT) with [99mTc]Tc-ADAPT6 and [99mTc]Tc-(HE)3-G3 in patients with HER2-positive breast cancer (BC) with axillary lymph node metastases. Materials and methods. The analysis included 8 patients with HER2-positive BC with axillary lymph node metastases before the systemic treatment. All patients were injected with [99mTc]Tc-ADAPT6 (500 µg) and [99mTc] Tc-(HE)3-G3 (3,000 µg) with an interval of 3–4 days. The SPECT-CT scans of the chest and upper abdomen were performed after 2 hours for [99mTc]Tc-ADAPT6 and after 4 hours for [99mTc]Tc-(HE)3-G3. The accumulation of radiopharmaceuticals was assessed by measuring the maximum standardized uptake values (SUVmax) in metastatic axillary lymph nodes, projections of the contralateral axillary lymph nodes, liver, latissimus dorsi muscle, and spleen. Additionally, mALN-to-background and mALN-to-reference organs ratios were calculated for each patient. Results. Comparison of the mALN-to-background ratio revealed the advantage of [99mTc]Tc-ADAPT6 (38.93 (16.56–56.02)) over [99mTc]Tc-(HE)3-G3 (19.39 (8.43–34.52)), p = 0.0391. The comparative analysis of the accumulation of the studied radiopharmaceuticals in the reference organs demonstrated higher SUVmax for [99mTc] Tc-(HE)3 -G3 in the liver and spleen (4.44 (2.85–9.08) and 2.47 (1.28–4.41), respectively) than for [99mTc]Tc-ADAPT6 (2.98 (1.96–3.65) and 0.43 (0.14–0.62), respectively), p = 0.01 and p = 0.04. Comparison of the SUVmax ratios in mALN and reference organs showed higher values of mALN / spleen for [99mTc]Tc-ADAPT6 (5.93 (1.04–11.85)) compared to [99mTc]Tc-(HE)3-G3 (1.83 (0.46–4.54)), p = 0.02. Conclusion. According to the results of the performed analysis, the diagnostic advantage of [99mTc]Tc-ADEPT6 for the detection of) HER2/neu expression in metastatic lymph nodes in breast cancer patients was revealed.